Konkret oder abstrakt? Externe Repräsentationen bei der Informationsentnahme und im Modellierprozess aus Lernerperspektive - Akman, Perihan

Selbstbau eines digitalen Low-Cost-Fotometers für den Chemieunterricht - Witte, Thomas; Hanemann, Stefan; Sommerfeld, Herbert; Temmen, Katrin; Fechner, Sabine (CHEMKON)
Keywords: digital; technology; teacher education

Generierung von Schülerfragen in lebenweltlichen Kontexten - Schmitz, Lisa; Fechner, Sabine (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe)

Die Wahrnehmung des Abstraktionsgrades von multiplen Repräsentationen - Akman, Perihan; Fechner, Sabine (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik, Jahrestagung in Kiel 2018)

Creativity in data analysis through confrontation with anomalous data - Pollmeier, Pascal; Fechner, Sabine (The beauty and pleasure of understanding: engaging with contemporary challenges through science education. Electronic Proceedings of the ESERA 2019 Conference.)
Creativity is perceived to be one of the core competences to succeed in the modern world. It is connected to art, music, dancing, etc., but there is just little insight into the role of creativity in science. As data analysis plays a major role in science, creative thinking has to be used to form theories out of observations. This study uses models-of-data to represent the mental model of the students. Within models-of-data different observations and previous knowledge are linked through different types of links, e.g. causal links. The goal of this study was to examine the creative aspect of data evaluation in presence of anomalous data. The students were confronted with two experiments which contradicted each other with regard to the underlying theory. Afterwards the students were asked to decide about their favored theory and reasoning about their choice in their lab reports. The model-of-data, which was reconstructed from the lab reports of the students, was used to extract creative aspects in the mental modelling process. Furthermore, a pre-post-questionnaire on epistemological beliefs of the students was conducted. Students mostly acquired an unscientific view on epistemology in school. The question was whether the confrontation with anomalous data and the triggering of creative modelling processes have any influence on this. The results show that most students did not take anomalous data into account in their modelling processes. They did either not recognise or just ignore the data. Just a few students worked on their theory because of the new, contradictory data. The students working on their theory scored higher in the post-questionnaire, so a positive effect of creativity on scientific epistemology can be assumed. Thus, creativity obviously gets a part of science and should be taught in school science in order to make students aware of their own creative potential.
Keywords: epistemology; conceptual change; anomalous data

Enkodierung chemischer Konzepte aus lebenweltlichen Kontexten - Kehne, Franziska; Fechner, Sabine (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik, Jahrestagung in Kiel 2018)

Analyse des Transfers von kontextualisiert erworbenem Wissen im Fach Chemie - Kehne, Franziska

Mentale Modelle - Nitz, Sandra; Fechner, Sabine (Theorien in der naturwissenschaftsdidaktischen Forschung)

Concrete and abstract external respresentations in chemistry education - Akman, Perihan; Fechner, Sabine (Electronic Proceedings of the ESERA 2017 Conference. Research, Practice and Collaboration in Science Education, Part 1 (co-ed. Finlayson, O. & Roser, P.))

Identifiction of students‘ questions in context-based learning approaches - Schmitz, Lisa; Fechner, Sabine (Electronic Proceedings of the ESERA 2017 Conference. Research, Practice and Collaboration in Science Education, Part 2 (co-ed. Tytler, R. & Carvalho, G. S.))

Science teaching processes (part 3). In Finlayson, O. E., McLoughlin, E., Erduran, S., Childs, P. (Eds.), Electronic Proceedings of the ESERA 2017 Conference. Research, Practice and Collaboration in Science Education

Context characteristics and their effects on students’ situational interest in chemistry - Habig, Sebastian; Blankenburg, Janet; van Vorst, Helena; Fechner, Sabine; Parchmann, Ilka; Sumfleth, Elke (International Journal of Science Education)

Generation of students' questions through real-life contexts and their potential use for sustainability issues in chemistry education - Schmitz, Lisa; Fechner, Sabine (Building bridges across disciplines for transformative eduction and a sustainable future)
Keywords: sustainability education; students' questions

Unterscheidung von Kontexten für den Chemieunterricht - van Vorst, Helena; Fechner, Sabine; Sumfleth, Elke (Zeitschrift für Didaktik der Naturwissenschaften)

Enhancing students' knowledge by meta-conceptual instruction - Dettweiler, Yvone

Egg-races als gesellschaftsfähige naturwissenschaftliche Wettbewerbe für jedermann? - Fechner, Sabine; Dettweiler, Yvonne; Sieve, Bernhard; Ulrich, Nina; Böhm, Dominic; Schanze, Sascha (CHEMKON)

Trendbericht Chemiedidaktik: Von Exklusion zur Inklusion - Becker, Hans-Jürgen; Fechner, Sabine; Brauckschulze, Lisa (Nachrichten aus der Chemie)

Science teaching processes - Introduction to strand 3. In Lavonen, J., Juuti, K., Lampiselkä, J., Uitto, A., & Hahl, K. (eds.), Electronic Proceedings of the ESERA 2015 Conference. Science education research: Engaging learners for a sustainable future.

Effects of innovative science and mathematics teaching on student attitudes and achievement: A meta-analytic study - Savelsbergh, Elwin R.; Prins, Gjalt T.; Rietbergen, Charlotte; Fechner, Sabine; Vaessen, Bram E.; Draijer, Jael M.; Bakker, Arthur (Educational Research Review)
Keywords: innovation; STEM education; science education; attitudes

Science Kits: Learning chemistry in a context-oriented learning environment - Fechner, Sabine; Sumfleth, Elke (Teachers creating context-based learning environments in science)